Investigation of Curing Process of Silver Conductive ink on Polymer Substrates using Halogen Lamp and Oven - Eraman, Siti Nur Elida; Khirotdin, Rd Khairilhijra’ (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The use of conductive silver ink has lately become popular in a variety of electrical applications. They are often sold in liquid form and need curing by heating to reveal their metallic components, with solvent residues remaining after curing for a few hours before thoroughly vaporizing. Halogen light and an oven were used to cure silver conductive ink on a polymer substrate, and the results of this research were presented in this article. The curing parameters were determined, and the impact of these factors on the conductivity, adhesion, and hardness level of the ink track was assessed. The connection between curing time and temperature to resistance has also been effectively established, demonstrating that the resistance of conductive ink track is proportionate to the length of curing time and temperature. In this study, it was discovered that the Oven is capable of generating a good curing process. When the temperature is raised, the amount of time it takes to cure the ink is lowered significantly. With less damaged polymer substrate, the optimal temperature and duration for curing silver conductive ink were 110°C for 90 minutes, and the lowest resistance achieved was 0.9Ω with the least amount of damage. According to the mechanical test, all of the results obtained in the Oven are entirely cured. It demonstrates that the Oven may be utilized as a preferred curing method in this study to adequately cure silver conductive ink on polymer substrates, as shown in the results.